2019
DOI: 10.1371/journal.pone.0220259
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rat glutathione transferases in olfactory epithelium and mucus

Abstract: The olfactory epithelium is continuously exposed to exogenous chemicals, including odorants. During the past decade, the enzymes surrounding the olfactory receptors have been shown to make an important contribution to the process of olfaction. Mammalian xenobiotic metabolizing enzymes, such as cytochrome P450, esterases and glutathione transferases (GSTs), have been shown to participate in odorant clearance from the olfactory receptor environment, consequently contributing to the maintenance of sensitivity tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
3
27
0
1
Order By: Relevance
“…It is unlikely that UGT could be present in the mucus because its activity has been shown to be dependent to the surrounding phospholipids in the membrane [ 30 32 ]. Accordingly, proteomic studies did not evidence UGT protein in the mucus in rat or human [ 4 , 33 35 ], while, as confirmed by our results, UGT2A1 has been detected in olfactory cilia proteome [ 36 , 37 ]. One should note that cross-reactivity of the antibodies with the UGT2A2 variant cannot be ruled out.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is unlikely that UGT could be present in the mucus because its activity has been shown to be dependent to the surrounding phospholipids in the membrane [ 30 32 ]. Accordingly, proteomic studies did not evidence UGT protein in the mucus in rat or human [ 4 , 33 35 ], while, as confirmed by our results, UGT2A1 has been detected in olfactory cilia proteome [ 36 , 37 ]. One should note that cross-reactivity of the antibodies with the UGT2A2 variant cannot be ruled out.…”
Section: Discussionsupporting
confidence: 78%
“…to the xenobiotic, Phase II (GST, UGT, etc) catalyze the subsequent conjugation of polar group (glutathione, glucuronic acid, etc). Mainly localized in the liver, their presence and activity toward volatile odorant substrates has been also evidenced at a high level in the olfactory tissues even higher for some isoforms [1][2][3][4][5]. There is an increasing body of proof demonstrating the main function of these odorant metabolizing enzymes (OMEs) in the physiology of olfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this vision, enzymes also involved in xenobiotic metabolism phase I demonstrated an interface between detoxification function, olfactory perception, and neurodegenerative and psychiatric disorders. In fact, animal models showed that the inhibition of rat CYP P450 monooxygenases increased the electro-olfactogram response amplitude, suggesting a role for these enzymes in signal termination [97], and that an odorant metabolite resulting from the cytochrome-dependent metabolism was able to activate an olfactory receptor [98,99]. CYP2D6, which is present not only in liver, but also at lower levels in brain and other tissues [40,100], metabolizes a wide variety of substances including therapeutic drugs, drugs of abuse, procarcinogens, and neurotoxins [40], and is genetically polymorphic [101].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wanted to explore specific proteins that have been implicated in odorant transport or metabolism across animal studies. [9][10][11] Lipocalin-15, which has been suggested to function as an OBP, 14,27,28 was found to be lower in patients with CRSsNP than controls (Table 2). Similarly, we found patients with CRS to have lower levels of glutathione S-transferases (GSTs), alcohol/aldehyde dehydrogenases, and other antioxidant proteins (Table 2), all of which have been postulated to impact olfaction by functioning as olfactory metabolizing enzymes in olfactory mucus.…”
Section: Crssnp Vs Controlsmentioning
confidence: 99%